A Decoupling method using Split Ring Resonator (SRR) for Tri-band MIMO Antenna for WLAN LTE Band and 5G applications - A. C. J. Malathi; B. V. K. Reddy; K. R. Phanindra (Advanced Electromagnetics, 2024)
MIMO antenna design has always been a topic of interest in wireless technology. Although it has many benefits, the key challenge is to minimize mutual coupling between antenna elements. This study presents a decoupling technique between two tri-band antennas for LTE, WLAN, and 5G applications. For 3.5GHz, a monopole is initially created; the other two resonant frequencies are produced by changing the partial ground plane. Then, a MIMO antenna system is created using two tri-band monopoles. The resonators of low band can minimize the mutual coupling for two higher bands by suppressing surface wave propagation. Finally, coupling is reduced in the low band by using a Split Ring Resonator (SRR) to cancel out the original coupling. The reported MIMO antenna spans the 2.4/5.8GHz WLAN and LTE bands, as well as the 3.5 GHz 5G bands, with a mutual coupling of less than -18 dB.